The theoretical framework for bilingual social issues studies - Uiego, Zh. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The changing geographical, demographic, economic, political, cultural and other factors affect the process of bilingualism in their own way and collectively influence the history, current situation and future of a certain bilingual phenomenon. When different language groups coexist, geographical factors \ shape people's activity area and language usage and sharing and the distribution patterns of ethnicities and language groups affect the distribution patterns of bilingualism. The economic activities among different ethnic groups promote the development of bilingualism and the languages of countries with higher the level of economic development will be more likely to spread. The state apparatus can affect the language usage and cultural development in a country through various education program and cultural events. The culture and religions have influence on improving people’s cohesiveness and formation of national consciousness, religious consciousness and language consciousness, which then exerts important effect on the types and development of bilingualism.
Қостілділікті əлеуметтік мəселе ретінде зерттеудің теориялық негіздері
Теоретические основы изучения двуязычия как социальной проблемы
Keywords: bilingualism; social issues; theoretical framework; economic factors; national identity